Drug development concerning metallo-β-lactamases in gram-negative bacteria - Li, Xiuyun; Zhao, Jing; Zhang, Bin; Duan, Xuexia; Jiao, Jin; Wu, Weiwei; Zhou, Yuxia; Wang, Hefeng (Frontiers in Microbiology, 2022)
β-lactams have been a clinical focus since their emergence and indeed act as a powerful tool to combat severe bacterial infections, but their effectiveness is threatened by drug resistance in bacteria, primarily by the production of serine- and metallo-β-lactamases. Although once of little clinical relevance, metallo-β-lactamases are now increasingly threatening. The rapid dissemination of resistance mediated by metallo-β-lactamases poses an increasing challenge to public health worldwide and comprises most existing antibacterial chemotherapies. Regrettably, there have been no clinically available inhibitors of metallo-β-lactamases until now. To cope with this unique challenge, researchers are exploring multidimensional strategies to combat metallo-β-lactamases. Several studies have been conducted to develop new drug candidates or calibrate already available drugs against metallo-β-lactamases. To provide an overview of this field and inspire more researchers to explore it further, we outline some promising candidates targeting metallo-β-lactamase producers, with a focus on Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii. Promising candidates in this review are composed of new antibacterial drugs, nonantibacterial drugs, antimicrobial peptides, natural products, zinc chelators, etc., as well as their combinations with existing antibiotics. This review may provide ideas and insight for others to explore candidate metallo-β-lactamases as well as promote the improvement of existing data to obtain further convincing evidence.